Networking Fundamentals : Develop the Networking Skills Required to Pass the Microsoft MTA Networking Fundamentals Exam 98-366 - Davies, Gordon (Packt Publishing, Limited, 2019)
Networks are a collection of computers, servers, mobile devices or other computing devices connected with a view to sharing data. This book will help you get well-versed with the basic concepts of networking and will help you to pass Microsoft's MTA Networking Fundamentals Exam 98-366.